DEVELOPMENTS IN THE FIELD OF STEEL AND CAST IRON - E. B. Ten; V. D. Belov (Литьë и металлургия)
The article describes the use of a number of promising casting technologies applied to produce the castings of steel and cast iron with special properties. Such as, technology of centrifugal casting of large-size workpieces made of steel, forecasting method composition of slag in the smelting of high-manganese steels, method of complex modifying chromium cast irons, analysis of properties of perspective high-alloy aluminium cast iron.